SCREENING BAKTERI PENGHASIL AMILASE DARI SEDIMEN SUMBER AIR PANAS DONDANG MUARA JAWA - M Nur Yasin Fahrul Fhozi; Winni Astuti; Rahmat Gunawan (Jurusan Kimia FMIPA UNMUL, 2017)
The screening of amylase enzyme producing thermophilic bacteria from sediment of hot spring in Muara Jawa has been done. Screening has done by using selective media of starch, will show the formation of clear zones around the colonies by dripping the iodine solution. From alot colonies selected 1 colony with widest clear zone. Single colony obtained was identified as Bacillus sp. Amylase produced was tested for amylase activity by DNS method and obtained the amylase activity at pH 6 and temperature at 55°C is 2,8460 U/mL.